2022
DOI: 10.3390/biomedicines10102642
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Adiponectin and Leptin Roles in Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is commonly associated with a high burden of comorbidities and poor clinical outcomes. Malnutrition–inflammation–atherosclerosis syndrome is common in the more severe stages of CKD, suggesting a close interplay for these three comorbid conditions. Both malnutrition and obesity are associated with a disturbed adipokine profile and inflammation, contributing to a higher risk of cardiovascular disease (CVD) events. Adiponectin and leptin have important roles in carbohydrate and lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 126 publications
0
11
0
Order By: Relevance
“…The uremic milieu can disrupt adipocyte metabolism, leading to pathogenic consequences. In CKD populations, increased adiponectin production occurs in both visceral and subcutaneous adipose tissues, while circulating adiponectin levels in pre-dialysis CKD patients negatively correlate with eGFR [ 31 ]. Nevertheless, the impact of elevated adiponectin levels on CKD patients’ metabolism remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uremic milieu can disrupt adipocyte metabolism, leading to pathogenic consequences. In CKD populations, increased adiponectin production occurs in both visceral and subcutaneous adipose tissues, while circulating adiponectin levels in pre-dialysis CKD patients negatively correlate with eGFR [ 31 ]. Nevertheless, the impact of elevated adiponectin levels on CKD patients’ metabolism remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…One plausible hypothesis for the association between high serum adiponectin concentrations and adverse CV outcomes in CKD patients is the development of adiponectin resistance, especially among those undergoing dialysis, owing to the uremic environment. An alternative explanation is that adiponectin secretion rises significantly to counterbalance the effects of heightened inflammatory cytokines and/or vascular injuries, but the inflammatory environments and proatherogenic uremic might overpower its effects [ 31 ]. Our study showed that as the CKD stage progressed, the serum adiponectin levels elevated and serum adiponectin levels are negatively associated with eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…In our another publication (in the press) we connected this fact with significantly higher serum concentration of leptin in this group which correlated positively with cystatin C concentration. Hyperleptynemia has negative impact on kidney function [ 25 ] and may result in cystatin C concentration increase in the group I. Cystatin C is considered an earlier and more accurate marker of GFR than creatinine [ 26 ]. In our study no significant correlation between this marker of renal function and lipid parameters was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin stimulates endocapillary proliferation and mesangial collagen deposition in the glomerulus by stimulating TNF-beta, leading to glomerulosclerosis [ 65 , 66 ]. In CKD and ESRD, different adipokine profiles of elevated leptin and adiponectin levels are observed [ 67 ]. Furthermore, cachexia (lower BMI) in the setting of a uremic milieu has also been reported to elevate the adiponectin level.…”
Section: Postulated Mechanisms Behind Obese-related Hypertension and ...mentioning
confidence: 99%